Suitability of Long‐Term Frozen Rat Blood Samples for the Interrogation of Pig‐a Gene Mutation by Flow Cytometry. (27th September 2018) - Avlasevich, Svetlana L.; Torous, Dorothea K.; Bemis, Jeffrey C.; Bhalli, Javed A.; Tebbe, Cameron C.; Noteboom, Jessica; Thomas, Demetria; Roberts, Daniel J.; Barragato, Matthew; Schneider, Brett; Prattico, John; Richardson, Mary; et al.
Abstract : The rodent blood Pig‐a assay has been undergoing international validation for use as an in vivo hematopoietic cell gene mutation assay, and given the promising results an Organization for Economic Co‐operation and Development (OECD) Test Guideline is currently under development. Enthusiasm for the assay stems in part from its alignment with 3Rs principles permitting combination with other genotoxicity endpoint(s) and integration into repeat‐dose toxicology studies. One logistical requirement and experimental design limitation has been that blood samples required antibody labeling and flow cytometric analysis within one week of collection. In the current report, we describe the performance of freeze–thaw reagents that enable storage and subsequent labeling and analysis of rat blood samples for at least seven months. Data generated from three laboratories are presented that demonstrate rat erythrocyte recoveries in the range of 80–90%. Despite some loss of erythrocytes, Pearson coefficients and Bland–Altman analyses based on fresh blood vs. frozen/thawed matched pairs indicate that mutant cell and reticulocyte frequencies are not significantly affected, as the measurements are highly correlated and exhibit low bias. Collectively, these data support the effectiveness and suitability of a freeze–thaw procedure that endows the assay with several new advantageous characteristics that include: flexibility in scheduling personnel/instrumentation; reliability when shipping samples from in‐life facilities to analytical sites; 3Rs‐friendly, as blood from positive control animals can be stored frozen to serve as analytical controls; and ability to defer a decision to generate Pig‐a data until more toxicological information becomes available on a test substance. Environ. Mol. Mutagen. 60:47–55, 2019. © 2018 Wiley Periodicals, Inc.